PELATIHAN MENGHITUNG PAJAK PENGHASILAN PASAL 21 UNTUK SISWA/I SMA BHK - Dewi, Syanti; Melawati, Natasha; Mudita, Novi Rahayu Mudita (MADANI: Jurnal Pengabdian Kepada Masyarakat, 2023)
All levels of society are required to pay taxes, especially taxes that come from gross revenues received every month. Paying taxes is the obligation of all people to comply with applicable regulations, and lots of new tax regulations have emerged during the pandemic and after the pandemic. Income tax is a tax imposed by individual or individual taxpayers on the income they receive. In understanding the science of taxation, everyone can learn from school starting from the high school level. This year, we held counseling again for high school students regarding how to calculate income tax article 21, where this tax is imposed on the regular and irregular income they receive. In conveying the material, we present it in the form of theory and examples of very simple questions in calculating the tax. This offline learning can help students understand the material provided. This learning process helps them understand and facilitate their understanding of income tax article 21. The specific target in counseling is to provide broad knowledge and insight for high school students in class 11 (eleven) IPS, in calculating income tax article 21 correctly . The results of this activity can develop soft skills and hard skills in the world of accounting, and also increase knowledge for students in developing their potential in continuing their studies at universities.